An Examination of the Psychometric Properties and Validation of the Family Resource Scale for Families Seeking Assistance With Their Child's Behavioral Difficulties. (June 2019) - Patwardhan, Irina; Duppong Hurley, Kristin; Lambert, Matthew; Ringle, Jay L.
Psychometric properties of the 30-item Family Resource Scale (FRS) were examined in a sample of families seeking assistance for their child's behavioral difficulties ( N = 300). The FRS is a measure that assesses the adequacy of family resources across several contexts including intra-family support and personal resources. Our analyses supported a modified 29-item four-factor solution ( basic needs, extra money and time, time for family, and essential ) compared with the seven-factor solution provided by the developers. Results showed that families' perception of their resources as adequate across all domains was associated with better family functioning and less caregiver strain. Combined, our findings suggest modifications to the existent structure of the FRS.